Development of a whole-cell biocatalyst co-expressing P450 monooxygenase and glucose dehydrogenase for synthesis of epoxyhexane - Akasit Siriphongphaew (2018)
Oxygenases-based Escherichia coli whole-cell biocatalyst can be applied for catalysis of various commercially interesting reactions that are difficult to achieve with traditional chemical catalysts. However, substrates and products of interest are often toxic to E. coli, causing a disruption of cell membrane. Therefore, organic solventtolerant bacteria became an important tool for heterologous expression of such oxygenases. In this study, the organic solvent-tolerant Bacillus subtilis 3C5N was developed as a whole-cell biocatalyst for epoxidation of a toxic terminal alkene, 1-hexene. Comparing to other hosts tested, high level of tolerance towards 1-hexene and a moderately hydrophobic cell surface of B. subtilis 3C5N were suggested to contribute to its higher 1,2-epoxyhexane production. A systematic optimization of reaction conditions such as biocatalyst and substrate concentration resulted in a 3.3-fold increase in the specific rate. Co-expression of glucose dehydrogenase could partly restored NADPH-regenerating ability of the biocatalyst (up to 38% of the wild type), resulting in approximately 53% increase in specific rate representing approximately 22-fold increase in product concentration comparing to that obtained prior to an optimization. © Springer-Verlag 2012.